School-leaving certificates and vocational education and training – the role of firms as gatekeepers in Germany - Friedrich, Anett [Verfasser] (My University, 2025)
„The aim of this study is to examine the characteristics of firms that influence their hiring decisions regarding the share of newly hired apprentices with Abitur and maximum lower secondary certificates. The study uses 2,004 training firms of the BIBB Qualification Panel data from 2013 to 2018 to estimate fixed-effects regressions analysing the effect of firms’ qualification structures and recruitment problems on the share of newly hired apprentices with Abitur (highest German secondary school-leaving certificate) and maximum lower secondary certificates (in German maximal Hauptschulabschluss). The results indicate that firms with a higher qualification structure hire a higher share of apprentices with Abitur. However, the effect gets insignificant once controlling for the share of applicants with Abitur. Further, the study suggests that firms reduce their requirements on the school-leaving certificate of VET applicants when they suffer from unfilled training positions. Moreover, the share of applicants with Abitur and maximum lower secondary certificate has high explanatory power for the share of newly hired apprentices with these certificates. The study highlights the role of firms in facilitating the transition of young people entering dual VET in Germany, whereas most studies so far have focused on the individual level. Further, the study contributes to the understanding of firms’ hiring processes of apprentices beyond the question of whether a firm provides VET at all and could be used for designing labour market policy programs for youth.“ (author’s abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; G 1.2.3 Qualifikationsentwicklungen; 370; Ausbildungsbetrieb; Ausbildungsverhalten; Berufsausbildung; Bewerberauswahl; Schulabgänger; Schulische Qualifikation; Qualifikationsniveau; Qualifikationsstruktur; BIBB-Qualifizierungspanel